Normative and legal regulation of legal responsibility for unauthorized occupation of land plot - Хом’яченко, Світлана Іванівна; Часова, Тетяна Олександрівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2016)
Normative and legal regulation of legal responsibility for unauthorized occupation of land plot is considered in the article. The authors admit that unauthorized occupation of land plot is one of the most common kinds of violations of land and criminal legislation, for which the citizens and legal entities bear responsibility according to the law. In modern conditions of reforming of the current legislation active work of realization of policy for prevention of violations of the land legislation, including topical issue of unauthorized occupation of the land plot is carried out. Now the regulation of legal responsibility of unauthorized occupation of land plot demands detailed consideration. The aim of the article is the investigation of normative and legal regulation of legal responsibility for unauthorized occupation of land. An important instrument of settlement of disputes of unauthorized use of land, retrieval of legitimate rights and interests of people is a submission of recovery suits of damage from appropriate subjects of an offense. Besides, people whose rights have been violated because of an unauthorized occupation of land plot have a right to appeal to court not only for the purpose of compensation of a damaged property, as well as moral harm. According to courts, in the presence of the sufficient bases a court satisfies the claim about what the relevant decree is issued, and in case of lack of the bases a court refuses satisfaction of the claim. We can draw a conclusion that one of the most widespread violations of the land and criminal legislation is unauthorized occupation of land plots for which citizens and legal entities bear responsibility according to the law. Definition of the term of unauthorized occupation of land plots is considered in the Law of Ukraine "About the state control of use and protection of lands", however investigative and court practice confirm its imperfection and need of further modification. It is necessary to adapt the specified law according to standards of the current legislation as unauthorized occupation of land plot has already become a usual aspect of people’s life.